Roles of malate and aspartate in gluconeogenesis in various physiological and pathological states - Holeček, Milan (Metabolism: clinical and experimental, 2023)
Gluconeogenesis, a pathway for glucose synthesis from non-carbohydrate substances, begins with the synthesis of oxaloacetate (OA) from pyruvate and intermediates of citric acid cycle in hepatocyte mitochondria. The traditional view is that OA does not cross the mitochondrial membrane and must be shuttled to the cytosol, where most enzymes involved in gluconeogenesis are compartmentalized, in the form of malate. Thus, the possibility of transporting OA in the form of aspartate has been ignored. In the article is shown that malate supply to the cytosol increases only when fatty acid oxidation in the liver is activated, such as during starvation or untreated diabetes. Alternatively, aspartate synthesized from OA by mitochondrial aspartate aminotransferase (AST) is transported to the cytosol in exchange for glutamate via the aspartate-glutamate carrier 2 (AGC2). If the main substrate for gluconeogenesis is an amino acid, aspartate is converted to OA via urea cycle, therefore, ammonia detoxification and gluconeogenesis are simultaneously activated. If the main substrate is lactate, OA is synthesized by cytosolic AST, glutamate is transported to the mitochondria through AGC2, and nitrogen is not lost. It is concluded that, compared to malate, aspartate is a more suitable form of OA transport from the mitochondria for gluconeogenesis.
Keywords: Citrin; Urea cycle; maláty; Pyruvic Acid; Mitochondrial carriers; AGC2; Aspartic Acid; glukoneogeneze; kyselina asparagová; Glutamates; Lactic Acid; Oxaloacetate; Malates; glutamáty; kyselina pyrohroznová; Gluconeogenesis; kyselina mléčná